Integrating Artificial Intelligence into School Organizations – a Beneficial Change - Georgiana - Tatiana Bondac; Silvia Elena Iacob; Angela Luminita Moldovan Durnea (Risk in Contemporary Economy)
Thanks to new technological developments, artificial intelligence (AI) occupies an increasingly important place in everyday life, including in education. There are many promising uses of AI that foreshadow how it will transform education in the coming decades. AI can accelerate personalized learning, provide continuous assessment and feedback to students, and apply analytics algorithms to personalize learning so it can be tailored in real-time to student needs. This article aims to answer the question,,Is the integration of artificial intelligence in school organizations an advantageous change?”.